The vergence stability hypothesis (H3), tested with Eq 3: - Mohammed Safayet Arefin (22683505) (2025)
The model is illustrated by the lines. Because there are no main effects or interactions with focal switching depth, the lines are horizontal, indicating that when observers fixate a target, the EVA will be stable, regardless of the focal switching depth distance or vergence direction of the eye movement. x marks the intercept of each participant. Also see Fig 12.